The Most Amazing Hide And Seek Alphabet Book - Crowther, Robert (Penguin Group, 1977)
In these two classics from Robert Crowther, readers can lift the flaps and pull the tabs to find an alphabet$1 (Bs worth of animals$1 (Band any number of surprises. Frogs that leap, hens that peck, snakes that uncoil $1 (Bopen this book and discover how much more there is to the alphabet than meets the eye! Letters wear the colors, stripes, or patterns of familiar and unusual animals, hinting at the wildlife riding on pull-tabs and hiding behind flaps.s
Keywords: Alphabet; Concepts; Juvenile Fiction